Aristocracia, monasterios y conflictos por la tierra. Reforma eclesiástica y relaciones sociales en León (siglos XI-XII) - Mariel Pérez (Bulletin du Centre d’Études Médiévales d’Auxerre)
This paper examines a series of disputes over land between the Benedictine monastery of Sahagún and Leonese noble families in order to understand the transformations in the relationship between laymen and clerics in the Kingdom of Leon after the impact of the Gregorian Reform. The essay posits that those disputes were an expression of the development of a more competitive kind of relationship between the aristocrats and the monastery in which pious donations got integrated into a negotiated logic of reciprocal exchange.